Curriculum-Based Lesson Study for Social Science Teachers: A Proof of Concept - Tjipto Subadi; Sabar Narimo; Erlina Farida Hidayati (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to analyze the curriculum-based social science teacher training model with a lesson study approach at SMK Muhammadiyah Sukoharjo. The approach used is qualitative phenomenology which is engaged in micro studies. The design used is based on class action modification. The place of research is at SMK Muhammadiyah Sukoharjo. The subjects were social science teachers, while the informants were teachers, principals, and supervisors. Collecting data using document, observation, and interview methods. The data analysis uses the theory of first order understanding and second order understanding. Conclusions: 1) The curriculum-based social science teacher training model with a lesson study approach at SMK Muhammadiyah Sukoharjo uses lesson study modification, this model can increase the professionalism of social science teachers with a scientific cooperative learning approach using a problem-based learning strategy as indicated by the pretest score > 65 = 50 % and posttest score > 75 = 100 %.